Rivaroxaban vs. enoxaparin for preventing venous thromboembolism after hip fracture operations: a retrospective cohort study - Zheng, Xiaofeng; Wang, Lifu; Chen, Yinhua; Liu, Lijuan; Zhang, Zijiao; Xiao, Cong (Frontiers in Surgery, 2025)
IntroductionEmerging evidence suggests that rivaroxaban may be effective in preventing venous thromboembolism (VTE) in patients with orthopedic trauma, resulting in fewer bleeding complications. This study aimed to evaluate the efficacy and safety of rivaroxaban compared with enoxaparin in preventing VTE in patients undergoing hip fracture surgery.Materials and methodsThis single-center, retrospective cohort study included patients who received either oral rivaroxaban or subcutaneous injections of enoxaparin for VTE prophylaxis following hip fracture surgery from 2020 to 2023. The data obtained included patient demographics, fracture classification, time to surgery, and procedures performed. The main outcomes assessed were the incidence of VTE and hemorrhagic events and death within 30 days of surgery. The daily costs of the two types of medications were also recorded.ResultsA total of 166 patients were included. The incidence of VTE was 9.5% in the rivaroxaban group and 26.61% in the enoxaparin group. Hemorrhagic events occurred in 9.52% and 1.61% of patients in the rivaroxaban and enoxaparin groups, respectively. No deaths occurred in either group. The average daily cost of rivaroxaban was 26.49 ± 4.77 Chinese yuan, while that of enoxaparin was 75.24 ± 18.54 Chinese yuan.ConclusionIn this cohort study, rivaroxaban was found to be significantly more effective than enoxaparin in reducing postoperative VTE after hip fracture, but it was associated with a higher risk of hemorrhagic events. Additionally, the average daily cost of rivaroxaban was lower. To identify patients who will derive the maximum advantages from this treatment, larger prospective studies are needed.